Kewenangan Kemendagri Dan Kemenkuham Dalam Pengharmonisasian Raperda - Nugrahani, Ellen Lutya Putri; Mau, Hedwig Adianto; Candra, Mardi (Jurnal Penelitian Hukum Legalitas, 2023)
The number of local regulations that are not harmonious with higher laws and regulations, poor public interest, decency and even human rights has attracted the attention of many parties. One of them is related to the role of the Regional Office of the Ministry of Law and Human Rights (Kanwil Kemenkumham) in the process of harmonizing draft regional regulations (raperda). The existence of Article 58 Paragraph (2) of Law No.15 of 2019 is expected to bring positive changes considering that every draft regulation must be harmonized through the Regional Office of the Ministry of Law and Human Rights before being facilitated by the Provincial Government Legal Bureau. The results showed that the implementation of Raperda harmonization by the Regional Office of the Ministry of Law and Human Rights is still not optimal. This is due to various obstacles, including the existence of the Circular Letter of the Director General of Legislation is considered not to be a strong basis as an implementing regulation for harmonization by the Regional Office of the Ministry of Law and Human Rights. Another problem is the conflict of harmonization authority between the Ministry of Law and Human Rights and the Ministry of Home Affairs (Kemendagri).  To overcome these obstacles, it is necessary to submit recommendations addressed to the Director General of Legislation to make an agreement with the Director General of Regional Autonomy of the Ministry of Home Affairs, to prepare a Joint Decree (SKB) between the Minister of Law and Human Rights and the Minister of Home Affairs related to the Harmonization of Regional Draft Regulations. In addition, the Director General of Laws and Regulations of the Ministry of Law and Human Rights should immediately make implementing regulations through Amendments to Presidential Regulation of the Republic of Indonesia Number 87 of 2014 concerning Implementation Regulations of Law Number 12 of 2011 concerning the Formation of Laws and Regulations. The amendment to the Presidential Regulation is adjusted to the contents of Article 58 Paragraph (2) of Law No.15 of 2019.